Understanding Multiculturalism in a Family on Whatsapp Group in the Disruption Era - Indriani, Sri Seti; Prasanti, Ditha (Universitas Semarang, 2019)
The SW6 family spread in several locations creates multiculturalism on WhatsApp social media groups. This study tries to describe the meaning of multiculturalism family on the WhatsApp group for the family members. This study is qualitative type using virtual ethnographic approach to describe the reality. The results of the study reveal that the experience of communication experienced is referred to as an archipelago insight experience. Cultural intelligence is assessed from the personal activeness of family members and information shared. When talking about something outside of its cultural values, there are some of the family members who choose to be silent, there are some who choose to ask questions to understand, but there are some who directly express their feelings. Communication culture can also be seen from the personal activeness of each members, there is a silent reader, some respond when needed, some are positioned as followers and some are dominant.